A produção associada em Capão Verde : entre bananas, saberes e utopias - Neves, Camila Emanuella Pereira (2012)
Throughout human history, the world of work acquired connotations and specific settings, and especially with the consolidation of the capitalist mode of production work was marked by contradictions between the social relations of production and knowledge production. In other words, holders of the means of production was for scientific knowledge and historically constructed and to the owners, only, of the labor force remained to them the knowledge acquired on the job experience. The bourgeois ruling class has established a culture of work - knowledge, values, attitudes - what interested him / favored and to play it the working class, had the help of the school. By 1980, this mode of production announced its crisis and no longer used the available workforce, having to surrender to a restructuring of production. As a result, a growing share of workers of the layer popular now (re) create different strategies to produce life, including the associated production. To perform this study, the fundamentals in dialectical historical materialism as an instrument for interpreting reality, the assumption of Marx (1982) that the work is responsible for the humanization of man in the categorization of experience forged by Thompson (2002.1998) and work as an educational principle in depth by Gramsci (2006, 1991). The objective of this study is to identify the significance of production and associated knowledge from this experience. The field research was conducted with workers and workers who joined in a Community of Poconé - Mato Grosso (Green Cover) to produce derivatives of plantain. For this, we used as a case study methodology and conduct recorded interviews with 12 workers (as) with a green cover and two volunteers, specific readings and recording of field research in audio, video, photos and Fieldbook. We hope to contribute to the enhancement of knowledge, practices and cultures made by classes that provide new conceptions of the world and man and reflections on the possible formation of a new type of worker.